Inorganic gel-microorganism composite self-repairing agent as well as preparation method and application thereof

Through inorganic gel-microbial composite self-repairing agent, inorganic mineral gel and microbial mineralization activities, the problems of low compatibility and long repair time of crack self-repair in the existing technology are solved, and efficient and whole-region crack self-repairing effect is achieved.

CN119528473APending Publication Date: 2025-02-28JIANGSU UNIV OF SCI & TECH
View PDF 1 Cites 0 Cited by

Patent Information

Application Number
CN202411724112.1
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-11-28
Publication Date
2025-02-28

Smart Images

  • Figure CN119528473A_ABST
    Figure CN119528473A_ABST
Patent Text Reader

Abstract

The invention discloses an inorganic gel-microorganism composite self-repairing agent as well as a preparation method and application thereof. The self-repairing agent is prepared from the following substances in parts by weight: 60 to 70 parts of inorganic mineral, 1 to 2 parts of polyacrylamide, 13.5 to 14.25 parts of monosaccharide, 4.5 to 4.75 parts of microorganism and 10 to 20 parts of barite powder. The inorganic mineral comprises one or more of a calcium source, a silicon source and an aluminum source, and the atom molar ratio of calcium to aluminum to silicon in the calcium source, the silicon source and the aluminum source is (0.5-2): (0-0.5): 1. The preparation method comprises the following steps: preparing the component A and the component B; watering and maintaining; dipping in styrene-acrylic emulsion, and drying; soaking, taking out and drying. The hydrated calcium silicate gel and the hydrated calcium aluminosilicate gel which are formed by induction in the initial stage of repair are hydration products of Portland cement, and the problem of compatibility between the repair products and a matrix can be avoided to a great extent when the hydrated calcium silicate gel and the hydrated calcium aluminosilicate gel are used for filling the cracks with the hydrated calcium silicate gel and the hydrated calcium aluminosilicate gel.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to a self-repairing agent and a preparation method and application thereof, and specifically relates to an inorganic gel-microorganism composite self-repairing agent and a preparation method and application thereof. Background Art

[0002] Concrete materials are widely used in various infrastructure constructions and are one of the most widely used engineering materials. Most public infrastructures serving the national economy and society have a design life of 100 years. Concrete materials are composed of silicate cement, aggregates, water, admixtures, etc. They are typical brittle composite materials with low tensile strength. Improper construction or significant environmental changes during service can easily lead to microcracks in the material. The presence of microcracks destroys the integrity of the material and weakens its structural bearing capacity. Cracks also provide a convenient channel for the invasion of external water and air. Water flowing through the crack space will dissolve hydration products such as hydrated calcium silicate and calcium hydroxide, resulting in calcium dissolution in concrete. Under the erosion of external moisture, the hydration products dissolve and disintegrate, and the cracks gradually grow and expand. Microcrack damage gradually evolves into macro cracks, which completely loses the structural bearing capacity of the concrete structure and then withdraws from service. Therefore, effective crack control is an important guarantee for the durability of concrete materials.

[0003] At present, the treatment of crack diseases is mainly based on applying repair agents after manual exploration. This repair method is called passive repair, and its repair efficiency depends on the efficiency of manual exploration. In order to realize the intelligent repair of cracks, a method of adding admixtures to enable cracks to sense cracks and repair them actively has been proposed. Various repair components are added to the concrete matrix. When cracks occur, the intruding moisture or air stimulates the repair components to produce physical or chemical reactions, forming a solid phase medium to seal the cracks.

[0004] At present, crack self-repair products are mainly organic adhesives and inorganic minerals. The organic adhesive self-repair method can achieve fast and efficient bonding of cracks, but organic adhesives are usually less compatible with the concrete matrix and will gradually age, resulting in a reduction in the repair effect. In addition, it requires a specific packaging method to assemble it into capsules before it can be added to concrete. Since the adhesive does not have an expansion effect, it can only solidify around the capsule after release to form a bonding repair effect, forming each independent "single point repair" instead of repairing the entire section of the crack. Inorganic mineral self-repair has high compatibility with the matrix, but there are problems such as long repair time and uneven distribution of repair products. The application of microbial method in cement-based materials is seriously affected by the matrix. The highly alkaline hydration products seriously inhibit the activity of microorganisms. It can only be mineralized in the surface area of ​​the crack where the conditions are relatively mild, and the repair depth is shallow. Therefore, measures must be taken to transform the cracks or protect the microorganisms in order to achieve efficient mineralization. Other mineral repair methods require a long repair time to gradually close the cracks through secondary hydration or carbonization. This reaction takes a long time to fully stimulate the activity of the repair agent, and the early crack repair ability is relatively weak. Patent CN116835902A discloses a rapid self-repairing agent for marine reinforced concrete cracks and its preparation method. The raw material used is magnesium acetate, and it is intended to form a magnesium-aluminum hydrotalcite phase product for repairing cracks. This requires strict control of the magnesium content therein. Excess magnesium ions will react with calcium silicate hydrate to form magnesium silicate hydrate without gelling ability, which will instead form a corrosive effect.

[0005] In summary, there is an urgent need to develop an inorganic mineral admixture that can self-repair cracks across the entire area, so as to achieve efficient and highly compatible self-repair of cracks. Summary of the invention

[0006] Purpose of the invention: In order to overcome the deficiencies in the prior art, the purpose of the present invention is to provide an inorganic gel-microorganism composite self-repairing agent with good compatibility and good repair effect. Another purpose of the present invention is to provide a convenient and practical method for preparing an inorganic gel-microorganism composite self-repairing agent. Another purpose of the present invention is to provide an application of an inorganic gel-microorganism composite self-repairing agent in the self-repair of cracks in silicate cement concrete.

[0007] Technical solution: The inorganic gel-microorganism composite self-healing agent described in the present invention includes the following substances in parts by weight: 60-70 parts of inorganic minerals, 1-2 parts of polyacrylamide, 13.5-14.25 parts of monosaccharides, 4.5-4.75 parts of microorganisms, and 10-20 parts of barite powder; the inorganic minerals include one or more of a calcium source, a silicon source, and an aluminum source, and the atomic molar ratio of calcium, aluminum, and silicon in the calcium source, silicon source, and aluminum source is 0.5-2:0-0.5:1.

[0008] Further, the inorganic minerals include one or more of calcium nitrite, calcium acetate, sodium silicate, lithium silicate, potassium silicate, sodium metaaluminate, potassium metaaluminate, and aluminum silicate. The modulus of sodium silicate does not exceed 1.5.

[0009] Furthermore, the microorganism is one or more of Clostridium butyricum, symbiotic butyrate oxidizing bacteria, and symbiotic acetate oxidizing bacteria. The number ratio of Clostridium butyricum, symbiotic butyrate oxidizing bacteria, and symbiotic acetate oxidizing bacteria is 1:1:1-2.

[0010] Furthermore, the monosaccharide is xylose, glucose or fructose.

[0011] Furthermore, the apparent density of the inorganic gel-microorganism composite self-healing agent is 1900-2100 kg / m 3 .

[0012] The method for preparing an inorganic gel-microorganism composite self-repairing agent of the present invention comprises the following steps:

[0013] Step 1: Prepare the inorganic mineral calcium source, half of the polyacrylamide, monosaccharide, and microorganism into microspheres, and coat the outer layer with a mixed gelling material of sulphoaluminate cement and barite powder, with a pH value not exceeding 10, to obtain component A; prepare the inorganic mineral silicon source, aluminum source, and the remaining half of the polyacrylamide into microspheres, and coat the outer layer with a mixed gelling material of silicate cement and barite powder, to obtain component B;

[0014] Step 2, watering and curing the product obtained in step 1;

[0015] Step 3, immersing the product obtained in step 2 in styrene acrylic emulsion and drying;

[0016] Step 4, soaking the product obtained in step 3 in water, taking it out and drying it to obtain an inorganic gel-microorganism composite self-healing agent.

[0017] The invention discloses an application of an inorganic gel-microorganism composite self-repairing agent in self-repairing of cracks in silicate cement concrete.

[0018] Furthermore, the dosage of the inorganic gel-microorganism composite self-healing agent meets the following conditions:

[0019]

[0020] Where m is the dosage of the self-healing agent, ρ is the apparent density of the self-healing agent, V con. is the concrete volume, r is the radius of the self-healing agent, and k is the influence coefficient, ranging from 1.05 to 1.06.

[0021] Repair principle: First, by inducing the formation of inorganic mineral gel in the cracks, the crack solution environment is improved to create favorable conditions for microbial activity. Secondly, the microbial mineralization activity is initiated, and by utilizing the mutualistic relationship between different microorganisms, the substrate is metabolized in a gradient manner, and the carbon source substrate is gradually converted into calcium carbonate precipitation. Finally, the inorganic mineral gel reaction and the microbial mineralization reaction complement each other to achieve effective repair of the crack section. Barite powder is used to adjust the density, and the inorganic mineral gel, polyacrylamide, monosaccharide, and microorganisms have a synergistic effect.

[0022] By utilizing the high alkalinity of silicate cement concrete crack solution, after calcium, silicon and aluminum sources are introduced into the cracks, calcium ions, silicate ions and aluminate ions will quickly combine with hydroxide ions in the solution to form inorganic minerals such as hydrated calcium silicate and hydrated calcium aluminosilicate after entering the liquid phase. The generated inorganic minerals will combine with a large number of water molecules to form inorganic mineral gels. Inorganic mineral gels have good volume expansion capabilities due to the combination of a large number of water molecules, and can be directly accumulated inside the cracks to seal the cracks.

[0023] When the thickener dissolves in water, it will capture the reaction to form inorganic minerals to form a flocculation structure, which can prevent the flowing water from carrying the product out of the crack space and ensure the effective accumulation of the product inside the crack.

[0024] The formation of inorganic minerals consumes a large amount of hydroxide ions, which reduces the pH of the fracture solution from high alkalinity to weak alkalinity. At this time, the released microbial spores germinate and grow. First, Clostridium butyricum uses xylose as a substrate for growth metabolism, and xylose is decomposed into butyric acid and carbon dioxide. Butyric acid will react with hydroxide ions to maintain the weak alkaline environment of the liquid phase. Carbon dioxide will react with hydroxide ions and calcium ions in the solution to form calcium carbonate precipitation.

[0025] The formation of butyric acid provides nutrients for the syntrophic butyrate oxidizing bacteria, which can use butyric acid to react to form acetic acid and carbon dioxide. Similarly, acetic acid can be further used to maintain the weak alkaline environment of the crack. And carbon dioxide will be further converted into calcium carbonate to supplement the self-healing effect of the crack. Acetic acid will eventually be used by the syntrophic acetate oxidizing bacteria, decomposed into carbon dioxide, and converted into calcium carbonate precipitation.

[0026] Beneficial effects: Compared with the prior art, the present invention has the following significant features:

[0027] 1. The hydrated calcium silicate gel and hydrated calcium aluminosilicate gel induced in the early stage of repair are hydration products of silicate cement. Using them to fill the cracks can greatly avoid the compatibility problem between the repair product and the matrix;

[0028] 2. By directly adding soluble calcium salts, silicates and aluminates, there is no need for an active activation process. After being dissolved in water, they can directly react to form gels such as hydrated calcium silicate and hydrated calcium aluminosilicate, which reduces the difficulty of the reaction, increases the deposition rate, and solves the problem of slow repair of early cracks;

[0029] 3. Gels such as hydrated calcium silicate and hydrated calcium aluminosilicate are consistent with the physical phase of the matrix. This method avoids the incompatibility problem between the repair product and the matrix. In addition, inorganic ions have strong diffusion ability. This dissolution, diffusion and reaction are oriented to the entire crack area, avoiding the problem of single-point repair. Calcium ions, silicate ions, aluminate ions, etc. dissolved from the matrix can also participate in the repair reaction, forming an additional repair effect;

[0030] 4. The formation of inorganic mineral gel consumes a large amount of hydroxide ions, creating a suitable living environment for microorganisms;

[0031] 5. Microorganisms can migrate, metabolize and mineralize well in the crack space, greatly increasing the activity and mineralization range of microorganisms;

[0032] 6. The microbial mutual metabolism process using monosaccharides as carbon sources can achieve gradient decomposition and complete consumption of monosaccharides, converting them all into calcium carbonate precipitation, avoiding the situation where a large amount of carbon dioxide gas is generated in a short time and escaped due to the rapid metabolism of a single microorganism, thus avoiding the waste of substrates to a great extent;

[0033] 7. During the monosaccharide gradient consumption process, the produced butyric acid, acetic acid and other substances can continue to maintain the low alkaline conditions of the solution to meet their own needs. BRIEF DESCRIPTION OF THE DRAWINGS

[0034] Figure 1 It is the preparation principle diagram of the present invention;

[0035] Figure 2 It is a bar graph of crack water penetration resistance repair rate of the present invention;

[0036] Figure 3 is a histogram of crack area repair rate of the present invention;

[0037] Figure 4 is a bar graph of the repair rate of ultrasonic wave propagation velocity across cracks of the present invention;

[0038] Figure 5 It is a bar graph of the area distribution rate of the crack surface repair product of the present invention;

[0039] Figure 6 It is the XRD diagram of the repair product of the present invention. DETAILED DESCRIPTION

[0040] Unless otherwise specified, the materials, reagents, instruments, etc. used in the following examples can be obtained from commercial sources. Experimental methods without specific conditions in the examples are usually carried out under conventional conditions or under conditions recommended by the manufacturer.

[0041] Sodium silicate, CAS: 13517-24-3, Xilong Scientific Co., Ltd. Aluminum silicate, CAS: 1302-93-8, Shanghai McLean Biochemical Technology Co., Ltd. Calcium nitrite, CAS: 13780-06-8, Shanghai Aladdin Biochemical Technology Co., Ltd. Sodium aluminate, CAS: 11138-49-1, Shanghai McLean Biochemical Technology Co., Ltd. Polyacrylamide, Henan Jiubang Water Purification Materials. Calcium lactate, CAS: 5743-47-5, Tianjin Damao Chemical Reagent Factory. Sodium alginate, CAS: 9005-38-3, Sinopharm Chemical Reagent Co., Ltd. Calcium acetate, CAS: 5743-26-0, Tianjin Zhonglian Chemical Reagent Co., Ltd. Styrene acrylic emulsion, Acronal PRO 780CN, BASF (China) Co., Ltd. Xylose, CAS: 58-86-6, Wuhan Xingzhongcheng Technology Co., Ltd. Fructose, CAS: 7660-25-5, Wuhan Kemik Biopharmaceutical Technology Co., Ltd. Sulphoaluminate cement, SAC52.5, Dengdian Group Cement Co., Ltd.

[0042] Example 1

[0043] 100g of inorganic gel-microorganism composite self-healing agent, including 70g of inorganic minerals (70wt% by mass); 1g of thickener polyacrylamide (1wt% by mass), 4.75g of microorganisms (4.75wt% by mass), 14.25g of xylose (14.25wt% by mass), and 10g of barite powder (10wt% by mass) as a weight-bearing component.

[0044] The inorganic mineral components include: 7.62g calcium nitrite powder (calcium source), 19.28g sodium silicate powder (silicon source, modulus 1.4), 43.10g sodium aluminate (aluminum source). The molar ratio of calcium to silicon is 2.0, and the molar ratio of aluminum to silicon is 5.0. The microorganisms include Clostridium butyricum spores, symbiotic butyrate oxidizing bacteria, and symbiotic acetic acid oxidizing bacteria, with a quantitative ratio of 1:1:2.

[0045] like Figure 1 , a method for preparing an inorganic gel-microorganism composite self-repairing agent, comprising the following steps:

[0046] (1) 7.62g of calcium nitrite powder, 0.5g of polyacrylamide powder, 4.75g of microorganisms, and 14.25g of xylose were prepared into microspheres, and the outer layer was coated with a mixed cementitious material of sulphoaluminate cement and barite powder, and the overall particle size was not greater than 4.00mm, and the obtained self-healing agent component A. 43.10g of sodium aluminate, 19.28g of sodium silicate, and 0.5g of polyacrylamide were prepared into microspheres, and the outer layer was coated with a mixed cementitious material of silicate cement and barite powder, and the overall particle size was not greater than 4.00mm, and the obtained self-healing agent component B was obtained.

[0047] (2) The product obtained in step (1) is subjected to curing at room temperature by sprinkling water for 3 days.

[0048] (3) The product obtained in step (2) was immersed in styrene-acrylic emulsion for 24 hours, and then dried at 50° C. for 24 hours. The operation was repeated three times.

[0049] (4) Soak the product obtained in step (3) in water for 24 hours, take it out and dry it, and the preparation of inorganic gel-microorganism composite self-healing agent particles is completed. The apparent density of the obtained repair agent particles is 1997 kg / m 3 .

[0050] Application Example 1

[0051] The concrete mix ratio used in a certain project is: cement 461kg / m 3 , fine aggregate 512kg / m 3 , coarse aggregate 1252kg / m 3 , water 160kg / m 3 The tested fine aggregate volume is 0.205m 3 , the volume of coarse aggregate is 0.482m 3 The volume of fresh concrete paste is 1.015m 3 The aggregate volume is 0.687m 3 , the calculation process is as follows:

[0052] V agg. =V f +V s =0.205+0.482=0.687m 3

[0053] The average radius of the self-healing agent obtained in Example 1 is 0.002 m, and the apparent density is 1997 kg / m 3 , k takes the value of 1.05.

[0054] The optimum dosage of the self-healing agent is 45.3 kg / m 3 For the convenience of measurement, the dosage is determined to be 46kg / m 3 .

[0055]

[0056] According to the above calculation results, the self-repairing concrete mix ratio is determined as follows: cement 461kg / m 3 , self-repairing agent 46kg / m 3 , fine aggregate 466kg / m 3 , coarse aggregate 1252kg / m 3 , water 160kg / m 3 Based on this, the concrete mix ratio was tested. The slump of concrete without self-repairing agent was 180mm, and the density of fresh slurry was 2405kg / m 3 The slump of self-repairing concrete is 175mm and the density of fresh slurry is 2400kg / m 3 The addition of self-healing agent has no significant effect on the conventional properties of concrete.

[0057] According to the association standard T / CECS 973-2021 "Technical Specifications for the Application of Microbial Self-Healing Concrete", self-healing concrete specimens were prepared and cured for 28 days under standard conditions. After curing, cracks with a width of about 1.0 mm were prepared using the splitting method, and the crack width was fixed. The cracked specimens were cured under simulated tap water conditions to test the crack repair effect.

[0058] Example 2

[0059] 100g of inorganic gel-microorganism composite self-healing agent, including 60g of inorganic minerals (60wt% by mass); 2g of thickener polyacrylamide (2wt% by mass), 4.5g of microorganisms (4.5wt% by mass), 13.5g of xylose (13.5wt% by mass), and 20g of barite powder (20wt% by mass) as a weight-bearing component.

[0060] The inorganic mineral components include: 26.28g calcium acetate (calcium source), 33.72g sodium silicate (silicon source, modulus 1.5). The calcium-silicon atomic molar ratio is 0.5. The microorganisms include Clostridium butyricum spores, symbiotic butyrate oxidizing bacteria, and symbiotic acetate oxidizing bacteria, with a quantity ratio of 1:1:2.

[0061] A method for preparing an inorganic gel-microorganism composite self-repairing agent comprises the following steps:

[0062] (1) 26.28g calcium acetate powder, 1.0g polyacrylamide powder, 4.5g microorganisms, and 13.5g xylose were prepared into microspheres, and the outer layer was coated with a mixed cementitious material of sulphoaluminate cement and barite powder, and the overall particle size was not greater than 5.00mm, and the obtained self-healing agent component A. 33.72g sodium silicate and 1.0g polyacrylamide were prepared into microspheres, and the outer layer was coated with a mixed cementitious material of silicate cement and barite powder, and the overall particle size was not greater than 4.75mm, and the obtained self-healing agent component B was obtained.

[0063] (2) The product obtained in step (1) is subjected to curing at room temperature by sprinkling water for 3 days.

[0064] (3) The product obtained in step (2) was immersed in styrene-acrylic emulsion for 24 hours, and then dried at 50° C. for 24 hours. The operation was repeated three times.

[0065] (4) Soak the product obtained in step (3) in water for 24 hours, take it out and dry it, and the preparation of inorganic gel-microorganism composite self-healing agent particles is completed. The apparent density of the obtained repair agent particles is 2100 kg / m 3 .

[0066] Application Example 2

[0067] The concrete mix ratio used in a certain project is: cement 427kg / m 3 , fine aggregate 525kg / m 3 , coarse aggregate 1286kg / m 3 , water 175kg / m 3 The tested fine aggregate volume is 0.205m 3 , the volume of coarse aggregate is 0.476m 3 The volume of fresh concrete paste is 0.995m 3 The aggregate volume is 0.681m 3 , the calculation process is as follows:

[0068] V agg. =V f +V s =0.205+0.476=0.681m 3

[0069] The average radius of the self-healing agent obtained in Example 2 is 0.0025m, and the apparent density is 2100kg / m 3 , k is 1.06. The optimal dosage of the self-healing agent is 59.3 kg / m 3 For the convenience of measurement, the dosage of self-healing agent is determined to be 60kg / m 3 .

[0070]

[0071] According to the above calculation results, the self-repairing concrete mix ratio is comprehensively determined: cement 427kg / m 3 , Self-repairing agent 60kg / m 3 , fine aggregate 465kg / m 3 , coarse aggregate 1286kg / m 3 , water 175kg / m 3 Based on this, the concrete mix ratio was tested. The slump of concrete without self-repairing agent was 190mm, and the density of fresh slurry was 2410kg / m 3 The slump of self-repairing concrete is 200mm and the density of fresh slurry is 2400kg / m 3 The addition of self-healing agent has no significant effect on the performance of concrete.

[0072] According to the association standard T / CECS 973-2021 "Technical Specifications for the Application of Microbial Self-Healing Concrete", self-healing concrete specimens were prepared and cured for 28 days under standard conditions. After curing, cracks with a width of about 1.0 mm were prepared using the splitting method, and the crack width was fixed. The cracked specimens were cured under simulated tap water conditions to test the crack repair effect.

[0073] Example 3

[0074] 100g of inorganic gel-microorganism composite self-healing agent, including 70g of inorganic minerals (70wt% by mass); 1g of thickener polyacrylamide (1wt% by mass), 4.75g of microorganisms (4.75wt% by mass), 14.25g of fructose (14.25wt% by mass), and 10g of barite powder (10wt% by mass) as a weight-bearing component.

[0075] The inorganic mineral components include: 32.50g calcium nitrite (calcium source), 20.02g sodium silicate (silicon source, modulus 1.4), 17.48g aluminum silicate. The molar ratio of calcium to silicon atoms is 1.0, and the molar ratio of aluminum to silicon atoms is 1.0. The microorganisms include Clostridium butyricum spores, symbiotic butyrate oxidizing bacteria, and symbiotic acetate oxidizing bacteria, with a quantitative ratio of 1:1:2.

[0076] A method for preparing an inorganic gel-microorganism composite self-repairing agent comprises the following steps:

[0077] (1) 32.50g of calcium nitrite powder, 0.5g of polyacrylamide powder, 4.75g of microorganisms, and 14.25g of fructose were prepared into microspheres, and the outer layer was coated with a mixed cementitious material of sulphoaluminate cement and barite powder, and the overall particle size was not greater than 3.5mm, and the obtained self-healing agent component A. 20.02g of sodium silicate, 17.48g of aluminum silicate, and 0.5g of polyacrylamide were prepared into microspheres, and the outer layer was coated with a mixed cementitious material of silicate cement and barite powder, and the overall particle size was not greater than 3.5mm, and the obtained self-healing agent component B was obtained.

[0078] (2) The product obtained in step (1) is subjected to curing at room temperature by sprinkling water for 3 days.

[0079] (3) The product obtained in step (2) was immersed in styrene-acrylic emulsion for 24 hours, and then dried at 50° C. for 24 hours. The operation was repeated three times.

[0080] (4) Soak the product obtained in step (3) in water for 24 hours, take it out and dry it, and the preparation of inorganic gel-microorganism composite self-healing agent particles is completed. The apparent density of the obtained repair agent particles is 2050 kg / m 3 .

[0081] Application Example 3

[0082] Concrete mix ratio of a certain project: cement 414kg / m 3 、Sand 704kg / m 3 、Stone 1213kg / m 3 , water 210kg / m 3 . According to the test, the volume of fine aggregate is 0.278m 3 , the volume of coarse aggregate is 0.458m 3 The volume of fresh concrete paste is 1.079m 3 The aggregate volume is 0.736m 3 , the calculation process is as follows:

[0083] V agg. =V f +V s =0.278+0.458=0.736m 3

[0084] The average radius of the self-healing agent obtained in Example 3 is 0.00175m, and the apparent density is 2050kg / m 3 , k is 1.055. The optimal dosage of the self-healing agent is 51.7 kg / m 3 For the convenience of measurement, the dosage of self-healing agent is determined to be 52kg / m 3 .

[0085]

[0086] According to the above calculation results, the self-repairing concrete mix ratio is comprehensively determined: cement 414kg / m 3 , self-repairing agent 52kg / m 3 , fine aggregate 652kg / m 3 , coarse aggregate 1213kg / m 3 , water 210kg / m 3 Based on this, the concrete mix ratio was tested. The slump of concrete without self-repairing agent was 190mm, and the density of fresh slurry was 2410kg / m 3 The slump of self-repairing concrete is 200mm and the density of fresh slurry is 2400kg / m 3 The addition of self-healing agent has no significant effect on the performance of concrete.

[0087] According to the association standard T / CECS 973-2021 "Technical Specifications for the Application of Microbial Self-Healing Concrete", self-healing concrete was prepared and cured for 28 days under standard conditions. The specimens after curing were prepared with cracks of about 1.0 mm in width according to the splitting method, and the crack width was fixed. The cracked specimens were cured under simulated tap water conditions to test the crack repair effect.

[0088] Example 4

[0089] 100g of inorganic gel-microorganism composite self-healing agent, including 70g of inorganic minerals (70wt% by mass); 1g of thickener polyacrylamide (1wt% by mass), 4.75g of microorganisms (4.75wt% by mass), 12.25g of fructose (12.25wt% by mass), and 13g of barite powder (13wt% by mass) as a weight-bearing component.

[0090] The inorganic mineral components include: 32.50g calcium nitrite (calcium source), 20.02g sodium silicate (silicon source, modulus is 1.0), 17.48g aluminum silicate. The molar ratio of calcium to silicon atoms is 1.0, and the molar ratio of aluminum to silicon atoms is 1.0. The microorganisms include Clostridium butyricum spores, symbiotic butyrate oxidizing bacteria, and symbiotic acetic acid oxidizing bacteria, and the number ratio is 1:1:1.

[0091] A method for preparing an inorganic gel-microorganism composite self-repairing agent comprises the following steps:

[0092] (1) 32.50g of calcium nitrite powder, 0.5g of polyacrylamide powder, 4.75g of microorganisms, and 12.25g of fructose were prepared into microspheres, and the outer layer was coated with a mixed cementitious material of sulphoaluminate cement and barite powder, and the overall particle size was not greater than 3.5mm, and the obtained self-healing agent component A. 20.02g of sodium silicate, 17.48g of aluminum silicate, and 0.5g of polyacrylamide were prepared into microspheres, and the outer layer was coated with a mixed cementitious material of silicate cement and barite powder, and the overall particle size was not greater than 3.5mm, and the obtained self-healing agent component B was obtained.

[0093] (2) The product obtained in step (1) is subjected to curing at room temperature by sprinkling water for 3 days.

[0094] (3) The product obtained in step (2) was immersed in styrene-acrylic emulsion for 24 hours, and then dried at 50° C. for 24 hours. The operation was repeated three times.

[0095] (4) After soaking the product obtained in step (3) in water for 24 hours, taking it out and drying it, the preparation of the inorganic gel-microorganism composite self-healing agent particles is completed.

[0096] Comparative Example 1

[0097] The remaining steps of this comparative example are the same as those of Example 1, except that no aluminum source is included.

[0098] Comparative Example 2

[0099] The remaining steps of this comparative example are the same as those of Example 1, except that the microorganisms are replaced by Bacillus subtilis powder of the same mass.

[0100] like Figure 2 to Figure 5 , the comparative example 1 with calcium source, silicon source and microbial component as the main components has a significant decrease in the repair effect compared with embodiments 1 to 3, especially for the distribution area rate of the repair product on the crack surface, the comparative example 1 is only about 1 / 3 of that of embodiments 1 to 3. The reason is that it is difficult to transmit gas deep in the crack, and Bacillus subtilis uses carbon dioxide in the air as a carbon source, which is difficult to mineralize inside the crack, resulting in a decrease in the repair effect. The comparative example 2 with calcium source, silicon source, aluminum source and Bacillus subtilis powder as the main components is greatly reduced compared with embodiments 1 to 3. The water seepage rate, surface repair rate, ultrasonic speed and other aspects have all decreased. In particular, the distribution area of ​​the repair product on the crack surface is greatly reduced. This is due to the replacement of microbial powder, which has led to the loss of a large amount of microbial mineralization activity to supplement the crack repair effect.

[0101] like Figure 6It can be seen from the XRD spectra of the repair products of Examples 1 to 3 that the main components of the products are CASH, CSH and CaCO3. In Example 1, due to the addition of silicon source and aluminum source, the characteristic peaks of CASH and CSH are significant, indicating that the gel deposition reaction has a good effect. The microorganisms also carried out effective mineralization and produced a large amount of calcium carbonate. In Example 2, only silicon source was added, so only CSH and CaCO3 were observed. In Example 3, silicon source and aluminum source were added, but the silicon source was added in the form of aluminum silicate, and the products were mainly CASH, CSH and CaCO3. In short, CASH and CSH are obtained by the reaction of the added inorganic minerals, indicating that the expected gel deposition reaction can be carried out effectively. Secondly, the presence of CaCO3 also proves that microbial mineralization activities can be carried out, which also shows that the gel deposition reaction as a pre-reaction creates a suitable physical and chemical environment for microbial mineralization, enabling it to induce the production of CaCO3 precipitation.

[0102] In general, the best embodiment is embodiment 3, which not only has advantages in various repair properties, but also can produce sufficient gel deposition material and calcium carbonate. The addition of aluminum silicate avoids the introduction of other impurity ions, and all ions participate in the gel deposition reaction, and the utilization efficiency of raw materials is higher.

Claims

1. An inorganic gel-microorganism composite self-repairing agent, characterized in that: The invention comprises the following substances in parts by weight: 60 to 70 parts of inorganic minerals, 1 to 2 parts of polyacrylamide, 13.5 to 14.25 parts of monosaccharides, 4.5 to 4.75 parts of microorganisms, and 10 to 20 parts of barite powder; the inorganic minerals comprise one or more of a calcium source, a silicon source, and an aluminum source, and the atomic molar ratio of calcium, aluminum, and silicon in the calcium source, silicon source, and aluminum source is 0.5 to 2:0 to 0.5:

1.

2. The inorganic gel-microorganism composite self-repairing agent according to claim 1, characterized in that: The inorganic minerals include one or more of calcium nitrite, calcium acetate, sodium silicate, lithium silicate, potassium silicate, sodium aluminate, potassium aluminate, and aluminum silicate.

3. The inorganic gel-microorganism composite self-repairing agent according to claim 2, characterized in that: The modulus of the sodium silicate does not exceed 1.

5.

4. The inorganic gel-microorganism composite self-repairing agent according to claim 1, characterized in that: The microorganism is one or more of Clostridium butyricum, symbiotic butyrate oxidizing bacteria, and symbiotic acetate oxidizing bacteria.

5. The inorganic gel-microorganism composite self-repairing agent according to claim 4, characterized in that: The quantity ratio of the Clostridium butyricum, the symbiotic butyrate oxidizing bacteria, and the symbiotic acetate oxidizing bacteria is 1:1:1-2.

6. The inorganic gel-microorganism composite self-repairing agent according to claim 1, characterized in that: The monosaccharide is xylose, glucose or fructose.

7. The inorganic gel-microorganism composite self-repairing agent according to claim 1, characterized in that: The apparent density of the inorganic gel-microorganism composite self-repairing agent is 1900-2100 kg / m 3 .

8. The method for preparing an inorganic gel-microorganism composite self-repairing agent according to any one of claims 1 to 7, characterized in that: The following steps are involved: Step 1: Prepare the inorganic mineral calcium source, half of the polyacrylamide, monosaccharide, and microorganism into microspheres, and coat the outer layer with a mixed gelling material of sulphoaluminate cement and barite powder, with a pH value not exceeding 10, to obtain component A; prepare the inorganic mineral silicon source, aluminum source, and the remaining half of the polyacrylamide into microspheres, and coat the outer layer with a mixed gelling material of silicate cement and barite powder, to obtain component B; Step 2, watering and curing the product obtained in step 1; Step 3, immersing the product obtained in step 2 in styrene acrylic emulsion and drying; Step 4, soaking the product obtained in step 3 in water, taking it out and drying it to obtain an inorganic gel-microorganism composite self-healing agent.

9. Use of the inorganic gel-microorganism composite self-repairing agent according to claim 1 in self-repair of cracks in silicate cement concrete.

10. The use of an inorganic gel-microorganism composite self-repairing agent according to claim 9 in self-repairing of cracks in silicate cement concrete, characterized in that: The dosage of the inorganic gel-microorganism composite self-repairing agent meets the following conditions: Where m is the dosage of the self-healing agent, ρ is the apparent density of the self-healing agent, V con. is the concrete volume, r is the radius of the self-healing agent, and k is the influence coefficient, ranging from 1.05 to 1.06.

Citation Information

Patent Citations

  • Rapid crack self-repairing agent for maritime work reinforced concrete and preparation method of rapid crack self-repairing agent

    CN116835902A